Pandemic-driven healthcare disruptions and their disproportionate impact on patients with diabetes: evidence from Texas - Saygili, Meryem; Gollu, Gultekin; Tekin, Zehra (Frontiers in Public Health, 2025)
BackgroundDiabetic Ketoacidosis (DKA) is a life-threatening complication of uncontrolled diabetes. The COVID-19 pandemic may have increased DKA incidences and worsened outcomes both through the potential diabetogenic effects of SARS-CoV-2 infection (direct effect) and through pandemic-related disruptions in healthcare (indirect effects,) including delays in seeking or receiving care, reduced access to routine outpatient services, and strains on hospital capacity. The objective of this study is to examine changes in the frequency and outcomes of hospitalizations with DKA in Texas hospitals following the COVID-19 pandemic and to quantify the contributions of pandemic-related healthcare disruptions and SARS-CoV-2 infection. Comparisons to patients with Acute Myocardial Infarction (AMI) and Acute Kidney Injury (AKI) were made to assess the disproportionate impacts of healthcare system disruptions on DKA patients.MethodsThis retrospective observational study uses regression analyses to evaluate the relative contributions of healthcare disruptions and viral infection on DKA frequency, in-hospital mortality, and length of stay. Event study and difference-in-differences models are employed to analyze whether DKA cases were disproportionately affected compared to patients with AMI or AKI. Quarterly inpatient discharge records from 2018 to 2021 are obtained from the Texas Department of State Health Services. Over 8 million discharge records are examined.ResultsDKA hospitalizations increased by 8% post-pandemic, with half of the increase attributable to pandemic-induced healthcare disruptions (indirect effects.) The average mortality of patients with DKA increased by 44% compared to the pre-pandemic average. Non-COVID channels contributed to a 30% increase in mortality. Compared to AMI and AKI patients, DKA patients were disproportionately affected by pandemic-induced disruptions.DiscussionThe COVID-19 pandemic significantly impacted DKA outcomes through the direct effects of SARS-CoV-2 infection and through various healthcare system disruptions—such as reduced access to routine diabetes care, delays in seeking treatment, and hospital resource constraints. Policies supporting uninterrupted diabetes management, such as telemedicine and medication access programs may reduce adverse outcomes in future health crises.